Gender in adoption of improved pigeon peas and its effect on food security Kenya. Issue 4 (19th May 2022) - Matere, Stella; Busienei, John R.; Irungu, Patrick; Mbatia, Oliver Lee Ernest; Kwena, Kizito
ABSTRACT: This paper examines the adoption of improved pigeon peas in female-headed households (FHHs) and male-headed households (MHHs) in semi-arid Kenya and its effect on yield as a proxy for household food security. Cross-sectional data were obtained from 450 households through a multi-stage sampling approach. We applied the endogenous switching regression model to establish the determinants of adoption decision and their effects on yield. Results showed that adoption increased crop yield. The adopting MHHs had significantly higher yield compared with the FHHs. The difference in yield was explained by both observed and unobserved characteristics in gender of the household head.